PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE TIPE THINK PAIR SHARE DI KELAS V SDN 27 PASAR KAMBANG KABUPATEN PESISIR SELATAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of fifth-grade students at SDN 27 Pasar Kambang, Pesisir Selatan Regency. This is due to the lack of active student involvement in the learning process due to teacher-centered learning, low critical thinking skills, and low self-confidence in expressing opinions and discussing with peers or groups. This study aims to describe the improvement in learning outcomes in Pancasila Education using the Think-Pair-Share Cooperative Model in fifth-grade students at SDN 27 Pasar Kambang, Pesisir Selatan Regency. This study was a Classroom Action Research (CAR) using two approaches: qualitative and quantitative. This study was conducted in two cycles: the first cycle consisting of two meetings and the second cycle consisting of one meeting, with four stages: planning, implementation, observation, and reflection. The subjects were 22 fifth-grade teachers and students at SDN 27 Pasar Kambang, Pesisir Selatan Regency. The results showed that the learning module aspect achieved an average score of 87.5% (B) in the first cycle, increasing to 95% (A) in the second cycle. In the aspect of teacher activity, cycle I obtained an average of 87.5% (A), increasing in cycle II to 95% (A). In the aspect of student activity, cycle I obtained an average of 87.5% (B), then increased in cycle II to 95% (A). Student learning outcomes in cycle I obtained an average of 71.1 (D), and increased in cycle II to 86.4 (B). It can be concluded that the Cooperative model of the Think Pair Share type can improve learning outcomes for Pancasila education in class V of SDN 27 Pasar Kambang, Pesisir Selatan Regency.